Service industries and Asia-Pacific cities : new development trajectories - Daniels, P. W.; Ho, Kong-Chong, 1955-; Hutton, T. A. (Thomas A.) (Routledge studies in the growth economies of Asia, 2005)
During the second half of the twentieth century, development in the Asia-Pacific region has been dominated by industrialization. However, at the beginning of the twenty-first century, services, in particular, finance, information and creative services, have become deeply embedded in the processes of urban growth. In Asia-Pacific the rise of service industries has lead to national modernization programmes and globalization strategies. Services are also driving change in the internal form of city regions and are being actively deployed as instruments of metropolitan reconfiguration and land use.